High thermal conductivity of boron nitride filled epoxy composites prepared by tin solder nanoparticle decoration. (15th November 2021) - Lee, Eun-Sung; Kang, Jong-Gu; Kang, Min-Kyeong; Kim, Ki-Hong; Park, Seon-Tae; Kim, Yong Su; Kim, In; Kim, Sung-Dug; Bae, Jin-Young
Abstract: To achieve a high thermal conductivity, thermally conductive polymer composites have been recently exploited, focusing on connecting a 3D network of thermally conductive fillers by applying external pressure or constructing a pre-made 3D filler framework to reduce phonon scattering within the polymer matrix. However, these approaches severely restrict the use of polymers, particularly epoxy composites, in many commercial applications such as the thermal management of electronic device packaging. In this study, a high-thermal-conductivity epoxy composite is fabricated by incorporating hexagonal boron nitride ( h -BN) decorated with tin nanoparticles (Sn NPs). Under a hybrid filler (Sn NPs on h -BN) loading (68 wt %), the composite exhibits a high thermal conductivity of 11.9 ± 0.29 W m −1  K −1 while maintaining a relatively low dielectric constant (Dk  ∼ 7.52) and loss (Df  ∼ 0.023) at 1 MHz with a coefficient of thermal expansion of 34 ppm °C −1 . The Sn NPs on h -BN in the epoxy resin matrix are thermally percolated by the in-situ growth of Sn NPs under carefully controlled curing temperature and time, resulting in significantly improved thermal conductivity of the epoxy composite under pressure-less curing conditions.